2000
DOI: 10.1021/ic990984x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Yttrium Chalcogenides:  Syntheses, Structures, and NMR Properties of Y[η3-N(SPPh2)2]3 and Y[η2-N(SePPh2)2]23-N(SePPh2)2]

Abstract: The compounds Y[N(QPPh2)2]3 (Q = S (1), Se (2)) have been synthesized in good yield from the protonolysis reactions between Y[N(SiMe3)2]3 and HN(QPPh2)2 in methylene chloride (CH2Cl2). The compounds are not isostructural. In 1, the Y atom is surrounded by three similar [N(SPPh2)2]- ligands bound eta 3 through two S atoms and an N atom. The molecule possesses D3 symmetry, as determined in the solid state by X-ray crystallography and in solution by 89Y and 31P NMR spectroscopies. In 2, the Y atom is surrounded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
2
23
0
2
Order By: Relevance
“…In contrast to the extensively studied N-bridged, monoanionic ligands [NA C H T U N G T R E N N U N G (PPh 2 E) 2 ] À (1, E= S, Se), which predominantly form E,E-chelated metal complexes without the participation of the N atom, [1,2] the isoelectronic C-bridged dianion [CA C H T U N G T R E N N U N G (PPh 2 S) 2 ] 2À (2) exhibits strong metal-carbon interactions in a variety of coordination complexes. The first example, a binuclear Pt II complex of 2, involved bis-C,S-chelation and a quaternary carbon bridging the two metal centres.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to the extensively studied N-bridged, monoanionic ligands [NA C H T U N G T R E N N U N G (PPh 2 E) 2 ] À (1, E= S, Se), which predominantly form E,E-chelated metal complexes without the participation of the N atom, [1,2] the isoelectronic C-bridged dianion [CA C H T U N G T R E N N U N G (PPh 2 S) 2 ] 2À (2) exhibits strong metal-carbon interactions in a variety of coordination complexes. The first example, a binuclear Pt II complex of 2, involved bis-C,S-chelation and a quaternary carbon bridging the two metal centres.…”
Section: Introductionmentioning
confidence: 96%
“…Unusual carbon-centred reactivity is also observed in the redox behaviour of compounds 2. In contrast with the formation of chalcogen-chalcogen bonds upon oxidation of Nbridged ligands of type 1, [11] treatment of Li 2 2 with the mild oxidising agents C 2 Cl 6 or I 2 produces remarkably stable monomeric or dimeric carbenoids, respectively. [12,13] The nu- Keywords: chalcogens · electronic structure · oxidation · radicals · tridentate ligands…”
Section: Introductionmentioning
confidence: 99%
“…[13] The diselenoimido-diphosphinato ligand can also stabilize a wide range of metal coordination spheres including alkali metals, [14][15] group 12, [16] group 13, [17,18] group 14, [19,20,16] group 15, [21] group 16, [22,23] transition metals (V and Cr, [24] Mn [25,26] and Re, [27] Ru, Rh, Ir, [15,28,29] Os, [30] Co, [31] group 10: Ni, [32] Pd, [32,[33][34][35] Pt, [14,30,34] and group 11: [35] , and rare earth metals. [36,37] This could be due to the flexible nature of the ligand moieties, which adopt to several metallacyclic rings depending upon the coordination to the central metal atom. We had recently reported that the missing group 2 metal complexes of di-selenoimidodiphosphinato ligand by synthesizing strontium and barium complexes via two synthetic routes -using diselenoimidodiphosphinato ligand with either silylamide or the salt metathesis route).…”
Section: Introductionmentioning
confidence: 99%
“…The fact is that coordination of the [N(EPPh 2 ) 2 ] À (E = O, S, Se) anions has been extensively studied over the last years. It has been found that the ligand N(SePPh 2 ) 2 binds a wide range of atoms varying from main group elements (K [2], group 12 [3]; Al and Ga [4], In [5], Sn [3,6], Pb [3], Sb [7], Bi [5,7], Se [8] and Te [9]), transition metals (V and Cr [10], Mn [11a] and Re [11], Ru [12], Os [13a,13b], Co [14], Rh [2,12b,12c], Ir [12b,15], group 10: Ni [16], Pd [2,12c,16,17], Pt [2,16,17], and group 11: Cu [14,18a] Ag [18a,18b,18c] Au [18b,18d,18e]) to rare-earth metals: Y [19], La, Gd, Er, Yb [20], and Sm [21]. Although the list of N(SePPh 2 ) 2 [22] complexes is certainly long, it is noteworthy the scarcity of metal carbonyl complexes with the N(SePPh 2 ) 2 fragment (or [N(EPPh 2 ) 2 ] À ; E = O, S for that matter).…”
Section: Introductionmentioning
confidence: 99%